Pengaruh Penggunaan Smartphone terhadap Prestasi Belajar Siswa MI Al-Falah Sambirobyong Nganjuk - Surur, Agus Miftakus; Lestari, Alifia Putri; Nabilah, Jihan Rona; Hamidah, Siti Nur; Akhyar, M. Khoiril; Ridwanulloh, M. Ubaidillah; Mohamed, Hasnah Binti (Journal Education And Islamic Studies, 2023)
A technology is essentially created to make human life easier and more comfortable. There is almost no area of ??human life that is free from its use, either directly or indirectly. This is also a result of the very rapid development of technology. Technology was created to facilitate every human activity. Born from human thoughts that try to facilitate their activities which are then applied in everyday life, one of which is in the teaching and learning process in schools. Thus in the learning process, technology can be used as a learning resource. Today, technology products have become a daily necessity in carrying out life activities. The use of cellphones and internet is not something strange or new anymore. Mobile is an electronic telecommunication device which has basic capabilities conventionally which is easy to carry and does not need to be connected to a telephone network using a cable. Mobile has a function to receive calls or SMS (short messages), cellphones can also function as a means of tracing, recording all activities, as a means of information and can even be used to explore the world of the internet depending on the features of the cellphone.